ZnO nanoparticles prepared via a green synthesis approach: Physical properties, photocatalytic and antibacterial activity. (January 2022) - Aldeen, Thana Shuga; Ahmed Mohamed, Hamza Elsayed; Maaza, Malik
Abstract: The aqueous extract of Phoenix roebelenii palm leaves has been utilized for the first time as an effective chelating/stabilizing agent used to synthesize zinc oxide nanoparticles (ZnO NPs) via a green chemistry approach. The physical properties of the nanoparticles were examined using X-ray powder diffraction (XRD), diffuse reflectance spectroscopy (DRS), high-resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED), simultaneous thermogravimetric analysis (TGA) and differential thermal analysis (DTA), photoluminescence (PL) spectroscopy, and Fourier transform infrared (FTIR) spectroscopy. Our XRD investigations revealed that the ZnO NPs have a single phase wurtzite structure with P63mc space group. The crystallite size and lattice strain were calculated using X-ray peak broadening analysis utilizing the Williamson-Hall (W-H) method and were found to be 15.6 nm and 2.1 × 10 −3 respectively. The shape of the ZnO NPs was almost spherical, as revealed by TEM analysis. The DRS spectrum showed a direct band gap energy of 3.24 eV. DTA/TGA indicated that the required calcination temperature was 500°C in order to form stable ZnO NPs. PL spectroscopy revealed the presence of weak UV emission related to the free exciton and wide visible-light emission due to oxygen vacancies and other structural defects. The reaction between P. roebelenii palm leaves extract and the zinc precursor was monitored using FTIR spectroscopy at different reaction times. The potential mechanism for the formation of the ZnO NPs using P. roebelenii leaves extract as a natural chelating and stabilizing agent has been discussed. The bioinspired ZnO NPs achieved an outstanding degradation activity of 98% toward methylene blue (MB) dye after 105 min of UV illumination. In addition, the ZnO NPs exhibit a significant bactericidal effect towards gram-positive ( Staphylococcus aureus and Streptococcus pneumoniae ) and gram-negative ( Escherichia coli and Salmonella typhi ) pathogenic bacteria. Highlights: ZnO NPs were successfully synthesized utilizing an extract of Phoenix roebelenii leaves. The formation reaction was monitored using FTIR spectroscopy and the mechanism was discussed based on the results. The pioneering photocatalytic efficiency of the ZnO NPs toward the degradation of MB was achieved. ZnO NPs exhibited a significant bactericidal effect towards several pathogenic bacteria.